2016
DOI: 10.1371/journal.pone.0166607
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Survey on Patient’s versus Physician´s Evaluation of Biological Therapy in Rheumatoid Arthritis in Relation to Disease Activity and Route of Administration: The Be-Raise Study

Abstract: ObjectivesBiological treatment of rheumatoid arthritis (RA) is one of the cornerstones of current treatment strategies for the disease. Surprisingly little information exists on whether the route of administration affects patients’ treatment satisfaction. It is equally unclear whether rheumatologists are able to accurately perceive their patients’ appreciation. Thus, the Belgian Be-raise survey aimed to examine whether RA patient’s experience of their current biological treatment coincided with the treating ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Results from the previous literature on patient and physician preferences for biologic therapy suggest a disconnect in patient and physician perceptions . Results of the 2 surveys reported here, along with the results of previous patient preference studies may address this disconnect by providing physicians with information regarding patients’ attitudes and concerns around different rheumatology treatments. This understanding of the patient perspective may help guide physicians’ discussions with their patients about different biologic therapy options.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Results from the previous literature on patient and physician preferences for biologic therapy suggest a disconnect in patient and physician perceptions . Results of the 2 surveys reported here, along with the results of previous patient preference studies may address this disconnect by providing physicians with information regarding patients’ attitudes and concerns around different rheumatology treatments. This understanding of the patient perspective may help guide physicians’ discussions with their patients about different biologic therapy options.…”
Section: Discussionmentioning
confidence: 59%
“…As previously noted, there is often a disconnect between patient and physician perceptions of IV therapy, with physicians presenting a more negative perception of IV therapy than that of patients who have been receiving IV therapy . Bridging this gap in patient and provider communication to ensure that the benefits, as well as risks, of both IV and SC options are presented to patients, to allow for a more balanced decision‐making process, could assist with improving biologic treatment adherence and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients and physicians have different perceptions and beliefs about health and illness [8][9][10][11]. Adequate understanding of patients' health perceptions and risk tolerance may assist physicians in the decision-making process at the time of the clinical encounters by helping them take into account benefit-risk ratios that are important to patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since patients are more likely to be satisfied and adhere to a treatment that is in line with their preferences [5,6], a patient-centered care approach, defined as 'providing care that is respectful of and responsive to individual patient preferences, needs, and values, ensuring that patient values guide all clinical decisions,' may have significant impact on treatment outcomes [7]. In RA, patient and physician assessment of disease severity and treatment response often do not align, suggesting that they focus on different aspects of the disease [8][9][10][11]. Values assigned by patients to their health status may be strongly driven not only by clinical aspects such as functional status or symptoms, but also by their beliefs and expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Matching treatment to patient preferences has been shown to improve adherence 5 6. Previous studies have shown that patient preferences for RA treatment vary widely and often differ from those of clinicians 7–11. Therefore, it is important that clinicians and patients make treatment decisions together using the best available evidence and accounting for patient preferences 12.…”
Section: Introductionmentioning
confidence: 99%